Comparative Study of Amorphous Calcium Phosphate-containing Orthodontic Composite and Conventional Orthodontic Adhesive on Enamel Demineralization around Orthodontic Brackets – An in vivo Study - Agarwal, Aradhana; Swami, Vinit; Sable, RB (Orthodontic Journal of Nepal, 2013)
Introduction: One of the most difficult problems in orthodontic treatment with fixed appliances is enamel demineralization around the brackets. This iatrogenically caused white spot lesions leads to poor esthetics; and in severe cases it may need restorative treatment. Objective: To evaluate in vivo effect of Amorphous Calcium Phosphate (ACP)-containing orthodontic composite on enamel demineralization around orthodontic brackets, and to compare it with the conventional resin based orthodontic composite. Materials & Method: 20 orthodontic patients planned for four first premolars extraction were selected for the study. All first premolars were bonded with Aegis Ortho, an ACP-containing orthodontic composite (experimental group), and Transbond XT, a resin-based orthodontic composite (control group). After 45 days teeth were extracted, sectioned for the microhardness group and evaluated by superficial-microhardness analysis and stereomicroscopic study. Unpaired t-test and analysis of variance (ANOVA) test was performed. Result: The ANOVA showed statistically significant differences for position, material, depth, and their interactions (p <0.001). The multiple comparison test showed that the ACP-containing orthodontic composite was significantly more efficient than the conventional composite, reducing enamel demineralization in almost all evaluations (p <0.001). The stereomicroscopic examinations showed a lesser extent of demineralization around orthodontic brackets for the ACP-containing orthodontic composite group. Conclusion: ACP-containing orthodontic composite for bonding orthodontic brackets successfully inhibited demineralization, which was localized to the area around the brackets.